ECTHR_COMMITTEE 48117/99 vom 25. September 2012 , AFFAIRE PEDICINI ET AUTRES c. ITALIE - Ecthr Committee (2012)
Violation of Article 6 - Right to a fair trial (Article 6 - Criminal proceedings;Article 6-1 - Reasonable time); Violation: 6;6-1